âARASIONâ (AUGMENTED REALITY FOR ANATOMY STUDY WITH SPEECH RECOGNITION) - Buana, Yudhisthira Cahya; P., Fendi Aji (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Augmented Reality (AR) is one of the latest information technology in multimedia section, and its implementation can be used in various fields. One of its achievement is that it has been developed in the world of education, as a more interactive and communicative learning media. The purpose of this study is to help students learning about human anatomy by making a learning system using Augmented Reality technology combined with Speech Recognition technology. This ARASION application was developed using several supporting software such as OpenSpace3D, Notepad++, Adobe Flash CS5, Adobe Photoshop CS4, CorelDRAW X4 and Autodesk 3ds max 2011. The concept of this application is to re-enact 3 dimensional objects of the human anatomy through a marker in the form of patterns/shapes, if the marker is detected by the camera/webcam and userâs input in speech recognition from entered then object will be displayed. The results of the study indeed help students in learning application of human anatomy using Augmented Reality technology and Speech Recognition.